Six weeks of polarized functional interval training with large training load reductions does not affect performance gains compared to traditional workouts - Steffen Held; Steffen Held; Eduard Isenmann; Eduard Isenmann; Ludwig Rappelt; Ludwig Rappelt; Tim Wiedenmann; Dominic Kutschki; Jannik Harbrecht; Katrin Kirchner; Stephan Geisler; Lars Donath (Frontiers in Physiology)
PurposeHigh-intensity functional interval training (HIFT) is predominantly composed of high exercise training intensities (HiT) and loads. Both have been linked to a higher risk of overtraining and injuries in inexperienced populations. A polarized training approach is characterized by high amounts of low-intensity training (LiT) and only approximately 5%–20% HiT. Compared to HIT-based training, this approach can result in temporary training load and intensity reductions without diminishing training gains. Thus, we aimed to examine the effects of traditional (TRAD) HIFT vs. polarized (POL) HIFT on relevant performance parameters.MethodsThirty athletes (15 females, age: 26.6 ± 5.0 years, height: 1.76 ± 0.13 m, body mass: 79.6 ± 12.4 kg, prior experience: 2.3 ± 2.0 years, training volume: 6.1 ± 2.4 h/wk) were randomly assigned to 6 weeks of either POL (78% LiT, 22% threshold intensity training (ThT) to HiT) or TRAD (26% LiT, 74% ThT to HiT). HIFT performance testing focused on maximal strength (squat: SQ1RM, deadlift: DL1RM, overhead press: OHP1RM, high pull: HP1RM), endurance (peak oxygen uptake: V̇O2peak, lactate threshold: LT, peak power output (PPO), and benchmark HIFT workout (Jackie: 1000 m rowing, 50 thrusters, and 30 pull-ups for time).ResultsPOL (785 ± 71 au) completed significantly (p ≤ 0.001; SMD = 4.55) lower training load (eTRIMP) than TRAD (1,273 ± 126 au). rANCOVA revealed no statistical relevant group×time interaction effects (0.094 ≤ p ≤ 0.986; 0.00 ≤ ηp2 ≤ 0.09) for SQ1RM, DL1RM, OHP1RM, high pull, V̇O2peak, LT, PPO, and Jackie performance. Both groups revealed trivial to moderate but significant (rANCOVA time effects: p ≤ 0.02; 0.01 ≤ ηp2 ≤ 0.11; 0.00 ≤ SMD ≤ 0.65) performance gains regarding DL1RM, OHP1RM, HP1RM, and Jackie.ConclusionDespite a notably lower total training load, conditioning gains were not affected by a polarized functional interval training regimen.